Application of Calcium Phosphate Materials in Dentistry - Al-Sanabani, Jabr S.; Madfa, Ahmed A.; Al-Sanabani, Fadhel A. (International Journal of Biomaterials, 2013)
Calcium phosphate materials are similar to bone in composition and in having bioactive and osteoconductive properties. Calcium phosphate materials in different forms, as cements, composites, and coatings, are used in many medical and dental applications. This paper reviews the applications of these materials in dentistry. It presents a brief history, dental applications, and methods for improving their mechanical properties. Notable research is highlighted regarding (1) application of calcium phosphate into various fields in dentistry; (2) improving mechanical properties of calcium phosphate; (3) biomimetic process and functionally graded materials. This paper deals with most common types of the calcium phosphate materials such as hydroxyapatite and tricalcium phosphate which are currently used in dental and medical fields.